Bahasa Dan Identitas Budaya Dalam Proyeksi Masa Depan: Pendekatan Futurologi Novel Bumi Cinta - Siddik, Achmad Muafi; Rizam, Masyithah Maghfirah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This research highlights the importance of preserving language and cultural identity in an increasingly powerful era of globalization. Globalization and information technology accelerate cultural interaction but also promote the homogenization of values thru the dominance of foreign languages. Using the novel Bumi Cinta as the research object, this study analyzes cultural encounters thru the characters of Ayas and Ilena. With a literary futurology approach, this research explores the role of language as resistance to globalization and the transformation of cultural identity. The novel "Bumi Cinta" by Habiburrahman El Shirazy was chosen as the research object because it presents the dynamics of cultural encounters thru its characters, particularly Ayas and Ilena, who explicitly display tension, resistance, and identity negotiation. This research uses a qualitative method with a literary futurology approach. The analysis focuses on the dialog, narrative, and cultural symbols contained in the novel, with language projected as a medium of resistance and transformation of cultural identity in the face of globalization. Data was obtained from the novel's text and analyzed interpretively using the theoretical frameworks of cultural identity and futurology. The research findings indicate that the character Ayas uses Indonesian and Arabic as a form of resistance against foreign cultural influences and as a symbol of collective identity resilience. Meanwhile, the character of Ilena reflects the process of negotiating and transforming identity thru her openness to learning Islamic language and values. The Moscow backdrop as a multicultural space reveals the interplay between local traditions and global influences. This finding confirms that language not only maintains cultural continuity but also serves as an instrument of cultural diplomacy capable of projecting the direction of future identity. Thus, literature plays a strategic role as both a medium of reflection and projection in maintaining and negotiating cultural identity in the era of globalization.